Case report of a dose-volume histogram analysis of rib fracture after accelerated partial breast irradiation: interim analysis of a Japanese prospective multi-institutional feasibility study - Yoshida, Ken; Otani, Yuki; Nose, Takayuki; Yoden, Eisaku; Asahi, Shuuji; Tsukiyama, Iwao; Dokiya, Takushi; Saeki, Toshiaki; Fukuda, Ichirou; Sekine, Hiroshi; Kumazaki, Yu; Takahashi, Takao; et al. (Journal of Contemporary Brachytherapy, 2018)
We initiated the first multi-institutional prospective study of accelerated partial breast irradiation for early breast cancer in Japan. Our early clinical results showed that the treatment methods were technically reproducible between institutions and showed excellent disease control at a median follow-up of 26 months in our previous report. At present, total 46 patients from six institutions underwent the treatment regimen from October 2009 to December 2011, and the median follow-up time was 60 months (range, 57-67 months). In 46 patients, we experienced one patient who had rib fracture as a late complication. The dose-volume histogram (DVH) result of this patient was analyzed. The D 0.01cc , D 0.1cc , and D 1cc values of the patient were 913, 817, and 664 cGy per fraction, respectively. These values were the highest values in 46 patients. The average D 0.01cc , D 0.1cc , and D 1cc values of the other 45 patients were 546, 500, and 419, respectively, cGy per fraction. From this result, DVH values showing high-dose irradiated volume (D 0.01cc , D 0.1cc , and D 1cc ) seem to be a good predictive factor of rib fracture for accelerated partial breast irradiation. However, further investigation is necessary because of the small number of patients investigated.